Intrinsic and damage-induced JAK/STAT signaling regulate developmental timing by the Drosophila prothoracic gland - Xueya Cao; Marta Rojas; José Carlos Pastor-Pareja (The Company of Biologists, 2022)
Development involves tightly paced, reproducible sequences of events, yet it must adjust to conditions external to it, such as resource availability and organismal damage. A major mediator of damage-induced immune responses in vertebrates and insects is JAK/STAT signaling. At the same time, JAK/STAT activation by the Drosophila Upd cytokines is pleiotropically involved in normal development of multiple organs. Whether inflammatory and developmental JAK/STAT roles intersect is unknown. Here, we show that JAK/STAT is active during development of the prothoracic gland (PG), which controls metamorphosis onset through ecdysone production. Reducing JAK/STAT signaling decreased PG size and advanced metamorphosis. Conversely, JAK/STAT hyperactivation by overexpression of pathway components or SUMOylation loss caused PG hypertrophy and metamorphosis delay. Tissue damage and tumors, known to secrete Upd cytokines, also activated JAK/STAT in the PG and delayed metamorphosis, at least in part by inducing expression of the JAK/STAT target Apontic. JAK/STAT damage signaling, therefore, regulates metamorphosis onset by co-opting its developmental role in the PG. Our findings in Drosophila provide insights on how systemic effects of damage and cancer can interfere with hormonally controlled development and developmental transitions.